2011
DOI: 10.1590/s0036-46652011000300007
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Allium sativum and Allium cepa in Schistosoma mansoni experimental infection

Abstract: SUMMARYThe effects of both garlic (Allium sativum) and onion (Allium cepa) on some biochemical parameters in Schistosoma mansoni infected mice individually and mixed either with or without the currently used drug, praziquantel (PZQ) were investigated. These involved some immunological parameters, namely IgM, IgG, interleukins 2 and 6 (IL-2 and 6) and tumor necrosis factor (TNF-α), some antioxidant enzymes [catalase, superoxide dismutase (SOD) and glutathione peroxidase (GPX)]. In addition, parasitological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 36 publications
8
47
1
Order By: Relevance
“…IL-2 supports the growth and expansion of B cells, as well as other immune cells, such as T cells, at varying stages of development or activation (46). In the present study, LEVA induced-IL-2 expression as it stimulated the immune system towards a type 1 response, and GO downregulated the expression of IL-2, which is consistent with its lowering effects on serum Ig and cytokine levels, and is in accordance with previously reported data when both LEVA and GO are administered (47).…”
Section: A B C D E F G H I Discussionsupporting
confidence: 93%
“…IL-2 supports the growth and expansion of B cells, as well as other immune cells, such as T cells, at varying stages of development or activation (46). In the present study, LEVA induced-IL-2 expression as it stimulated the immune system towards a type 1 response, and GO downregulated the expression of IL-2, which is consistent with its lowering effects on serum Ig and cytokine levels, and is in accordance with previously reported data when both LEVA and GO are administered (47).…”
Section: A B C D E F G H I Discussionsupporting
confidence: 93%
“…In consistence with our results Balkwill (2009); Mantawy et al (2011) reported that TNF-α is a proinflammatory cytokine activates signal transduction pathways, leads to apoptosis, cell proliferation, angiogenesis, cellular senescence, DNA damage and increase the metastatic potential of tumors in animal models reflect its higher significant increase at 16 and 18 weeks p.i. In general, constitutive exposure to high levels of pro-inflammatory cytokines is thought to be protumorigenic.…”
Section: Discussionsupporting
confidence: 91%
“…However, there should be numerous possibilities responsible for the reduction of eggs. The mentioned factors may be responsible for diminishing fecundity of the worm pairs and cause an increase in the rate of egg excretion according to the worm pairs (Mantawy et al, 2011). As displayed in Figure 1, the number of total worms including male and female worms were decreased in infected mice treated with AGE+ GOE (1015 ± 1.41) compared to infected untreated mice (1502 ± 2.13) notably.…”
Section: In Vivo Studiesmentioning
confidence: 95%
“…As displayed in Figure 1, the number of total worms including male and female worms were decreased in infected mice treated with AGE+ GOE (1015 ± 1.41) compared to infected untreated mice (1502 ± 2.13) notably. It was also reported that, the more immunoglobulins elevated there were, the more reactive oxygen was decreased in treatment of schistosomiasis, therefore, this mechanism can be happened through antioxidants defenses from infected hepatic cells increasing constant oxidative stress and oxidation of lipids, protein and other macromolecules such as DNA (Mantawy et al, 2011). Anemia was observed due to a strong decrease in the level of Hb percentage in infected untreated mice (7.6 ± 0.3, P≤0.05) compared to non-infected untreated mice (11.2 ± 0.2, P≥0.05) therefore it decreased the number of RBCs, Group VI treated with 125 mg kg1 of AGE (8.5 ± 0.4, P<0.001) showed the highest amount of WBCs compared to non-infected group, besides, the number of PVC was also decreased in untreated infected mice (33.54 ± 0.1, P≤0.01) in comparison with non-infected untreated mice (41.36 ± 0.6, P≥0.05).…”
Section: In Vivo Studiesmentioning
confidence: 99%